1986
DOI: 10.3109/00016348609155179
|View full text |Cite
|
Sign up to set email alerts
|

Menstruation Span – a Time‐Limited Risk Factor for Endometrial Carcinoma

Abstract: A case-control study was undertaken to investigate the influence of reproductive factors on the risk of developing endometrial carcinoma. The study comprised 254 women with newly diagnosed endometrial carcinoma, resident in a defined geographical area, and 254 age-matched population controls. Nulliparity and late menopause were positively associated with endometrial carcinoma. Each additional full-term pregnancy resulted in a decrease in the risk by 16%. The importance of parity and menopausal age decreased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
0
3

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 27 publications
8
35
0
3
Order By: Relevance
“…This may relate to less frequent anovulation among women who can conceive at older ages (Escobedo et al, 1991;Modan et al, 1998). Future investigations should focus on hormonal changes associated with pregnancy, taking note of our findings as well as others (Pettersson et al, 1986;Albrektsen et al, 1995;Lambe et al, 1999) of stronger effects of multiparity among younger women.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This may relate to less frequent anovulation among women who can conceive at older ages (Escobedo et al, 1991;Modan et al, 1998). Future investigations should focus on hormonal changes associated with pregnancy, taking note of our findings as well as others (Pettersson et al, 1986;Albrektsen et al, 1995;Lambe et al, 1999) of stronger effects of multiparity among younger women.…”
Section: Discussionsupporting
confidence: 61%
“…This factor has not generally been regarded as a predictor of endometrial cancer risk (Pettersson et al, 1986;Lesko et al, 1991;Brinton et al, 1992;Parazzini et al, 1998;Xu et al, 2004), despite a number of studies that have demonstrated relatively strong associations (Kvale et al, 1988;Parslov et al, 2000;Hinkula et al, 2002;Wernli et al, 2006). Although it is widely accepted that multiparity may reduce endometrial cancer risk through changes in hormonal profiles, including lowered estradiol and increased sex hormone binding globulin levels (Chubak et al, 2004), underlying mechanisms for reduced risks associated with delayed ages at a first birth are less clear.…”
Section: Discussionmentioning
confidence: 99%
“…The first relevant systematic review using the criteria of the US Preventive Services Task Force and evaluating the association between COCs and endometrial cancer was published in 1995 (Grimes & Economy 1995), assessing 13 case-control studies (Horwitz & Feinstein 1979, Kaufman et al 1980, Weiss & Sayvetz 1980, Hulka et al 1982, Kelsey et al 1982, Henderson et al 1983, LaVecchia et al 1986, Pettersson et al 1986, CASH 1987, Koumantaki et al 1989, WHO Collaborative Study 1991a,b, Brinton & Hoover 1993, Jick et al 1993, Maxwell et al 2006 and 3 cohort studies (Ramcharan et al 1981, Trapido 1983, Beral et al 1988; Fig. 1).…”
Section: Early Case-control and Cohort Studiesmentioning
confidence: 99%
“…Unopposed estrogen therapy (17)(18)(19) and tamoxifen (20,21), both of which exert proliferative effects on the endometrium, have also been associated with an elevated incidence of the disease. Conversely, increased parity (4,11,22,23) and combination oral contraceptive use (4,(24)(25)(26), both characterized by a relatively high degree of exposure to progestogens, are associated with reduced risk of endometrial cancer. Exposure to endogenous or exogenous estrogens not adequately opposed by progestogens leads to an increase in the mitotic activity of endometrial epithelial cells (27).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial epidemiologic data implicate an imbalance of estrogens and progestogens in the etiology of endometrial cancer (Table 1): early menarche (1, 2), late menopause (3,4), anovulation (5,6), prolonged menstruation, obesity (7)(8)(9), polycystic ovary syndrome (10), and diabetes mellitus (11)(12)(13), characteristics or conditions involving a relative increase in exposure to endogenous estrogens, have been associated with an increased risk of the disease. All three prospective studies that have examined hormone levels observed an increase in endometrial cancer risk with increasing circulating levels of estrogen (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%